The Effect of Migration on the Domestic Job Market: Evidence from Australia - Wasisto Raharjo Jati (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2023)
This paper aims at analysing the relationship between foreign workers and its implication for the domestic job market with Australia as the point of reference. The globalized era pushes every nation to open its market including the job market. This ongoing trend surely causes disruptions in the domestic market. At the same time, the wave of overseas migrant workers fulfills the job sectors which are rarely filled by domestic workers. It can encourage the transfer of knowledge from foreign to domestic laborers. On the other hand, more overseas workers threaten the existence of domestic employers. Australia has been in a dilemma position on this matter. Many foreign workers come in fulfilling the low-level job sectors, such as fruit handpicking, construction, and nursery. At the same time, their presence threatens domestic workers who could perform better in the same field. This especially occurs when they always ask for higher wages which might be irrelevant to the domestic business cycle. In order to analyze this problem, this paper used the quantitative method. The main findings of this paper show that when the government issues policies to encourage employers to spend more on human investment, it improves the work quality of domestic workers more than foreign ones. This suggests/concludes the way government should be protective and selective in securing the domestic job market from overseas migrant workers.